L’interpellation en français : un système comme les autres? - Reyes Leon Miranda (Corela)
My study is based on three oral corpora and one written corpus and it has a double objective. Firstly, nominal forms of address (FNA) (Kerbrat-Orecchioni, 2010, in press) will be analysed from the point of view of their pragmatic function(s) within the speech and their facial and gestural realisation. Secondly, facial and gestural forms of address (FMGA) will be introduced and analysed. These FMGAdo not have a nominal support in speech but represent a real way of addressing that fills the same, or even more, pragmatic functions as the FNA.